Level of Independence and Attitude in Fulfillment of Activity Daily Living with the Risk of Falling in the Elderly - Mareyke Y.L. Sepang; Wahyuny Langelo; Maharany Ungkey (GLOBAL HEALTH SCIENCE GROUP, 2021)
Changes in physical condition in the elderly cause the risk of falls in the elderly. The incidence of falls can hinder the quality of life of the elderly such as a decrease in independence in carrying out functional activities. The independence of the elderly in Lirung 1 Village was found to be still elderly who forced to carry out their activities independently even though their physical health conditions had weakened who should have needed assistance in carrying out daily activities or in fulfilling Activity Daily Living (ADL).The aim of this research is to determine the relationship between the level of independence and attitude in fulfilling Activity Daily Living with the risk of falling in the elderly in Lirung 1 Village, Talaud Island. This research is quantitative research with correlation research design. The data was collected by questionnaire tools used a Barthel Index questionnaire, attitude questionnaire and Morse Falls Scale (MFS). The population in this study were all the elderly in Lirung 1 Village, totaling 174 elderlies with sampling using purposive sampling technique, the number of samples taken is as many as 121 elderly respondents. This study uses the Spearman's Rho Correlation test. The results showed that the level of independence (p value 0,000) and the attitude (p value 0,000) with the risk of falling in the elderly. There is a relationship between the level of independence and attitudes in fulfilling daily living activities with the risk of falling in the elderly.